Gender of Prisoners Admitted to State and Federal Institutions in the United States, 1926-1987 ([Verlag nicht ermittelbar], 1991)
This data collection includes tabulations of annual adult admissions to federal and state correctional institutions by gender for the years 1926 through 1987. The two data files have identical structures: Part 1 includes information on male admissions, and Part 2 includes information on female admissions. The 3,348 cases in each part include one case for each of the 62 years of the collection for each of the following 54 categories: the 50 states, the District of Columbia, federal institutional totals, state cumulative totals, and United States totals (the sum of the federal and state cumulative totals). The figures were drawn from a voluntary reporting program in which each state, the District of Columbia, and the Federal Bureau of Prisons reported summary and detailed statistics, as part of the National Prisoner Statistics reporting series. Each file also includes individual state and United States general population figures.